2015
DOI: 10.1596/1813-9450-7170
|View full text |Cite
|
Sign up to set email alerts
|

Can We Measure Resilience? A Proposed Method and Evidence from Countries in the Sahel

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…crosssectional) did not guarantee an adequate measure of resilience as capacity. A slightly different analytical framework for resilience and food security is proposed by Alfani et al (2015). Motivating their framework on the grounds of consumption and income smoothing, the authors learn from the program evaluation literature and build their model on a counterfactual framework.…”
Section: Operationalizing and Measuring Resilience From A Household Fmentioning
confidence: 99%
“…crosssectional) did not guarantee an adequate measure of resilience as capacity. A slightly different analytical framework for resilience and food security is proposed by Alfani et al (2015). Motivating their framework on the grounds of consumption and income smoothing, the authors learn from the program evaluation literature and build their model on a counterfactual framework.…”
Section: Operationalizing and Measuring Resilience From A Household Fmentioning
confidence: 99%
“…Other quantitative approaches for measuring resilience exist. While a comprehensive review can be found in ILRI (2016), one of the most recent is Alfani, Dabalen, Fisker, and Molini (), which used cross‐section data from four countries in the Sahel region of Africa. In that study, the sample was divided into three groups: chronically poor, non‐resilient and resilient households, and the study used counterfactual welfare indexes at the household level before and after shocks.…”
Section: Resilience Measurementmentioning
confidence: 99%
“…These studies have focused on the following: identifying which economic units are or are not resilient; the differential impacts of shocks on these units; and the responses of different economic units to these shocks (Hoddinott 2006, Carter et al 2007, Akter and Mallick 2013, Alfani et al 2015, Jain et al 2015, Cissé and Barrett 2016. Analysis of this nature enables interventions to be targeted to increase the resistance of farmers to hazards, e.g., flood resistant seeds (Dar et al 2013) or enable ex post coping (e.g., Akter et al 2016).…”
Section: Discussionmentioning
confidence: 99%